2022
DOI: 10.3390/ejihpe12080077
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students’ Mental Health and Resilience in COVID-19: An Assessment after One Year of Online Education

Abstract: COVID-19 has impacted mental health and affected education due to the shift to remote learning. The purpose of the current study was to assess the mental health of pharmacy students one year following the onset of the pandemic. A descriptive cross-sectional questionnaire was distributed to pharmacy students. The severity of depression, anxiety, and stress was assessed by the Depression Anxiety Stress Scale (DASS-21), and resilience was assessed by the Brief Resilience Scale (BRS). COVID-19-related economic, ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
1
13
1
Order By: Relevance
“…The results were compared with other studies that assessed the same. In this study, most participants were younger than 22 years and were females, consistent with other studies conducted in Saudi Arabia and Lebanon (Alsahali, 2021;Hammoudi et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results were compared with other studies that assessed the same. In this study, most participants were younger than 22 years and were females, consistent with other studies conducted in Saudi Arabia and Lebanon (Alsahali, 2021;Hammoudi et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…The lack of accurate mental health awareness has been reported to be one of the leading factors that may contribute to categorizing people with mental illnesses (Girma & Tesfaye, 2011). Although several studies have assessed attitudes towards people with mental illness and knowledge about MIs (Alsahali, 2021;Hammoudi et al, 2022), data from Yemen are scarce. Therefore, the primary objective of this study was to assess pharmacy students' attitudes toward Mis, people with MIs, and seeking help for mental health.…”
Section: Anaammentioning
confidence: 99%
“…The prevalence of anxiety, depression, and stress was high among students in the online learning context after the pandemic. For instance, 70.7, 64, and 48.3% of pharmacy students reported mild-to-severe anxiety, depression, and stress levels in Lebanon (Hammoudi Halat et al, 2022 ) and 51.3% (anxiety), 29.4% (depression), and 56.5% (stress) of university students in Malaysia (Moy and Ng, 2021 ). However, regarding the prevalence of mental disorders among lecturers, only 15.7, 17.6, and 21.6% of them showed anxious, depressive, and/or stress-related symptoms (Miguel et al, 2021 ), which was much less than that of students.…”
Section: Discussionmentioning
confidence: 99%
“… 17 A survey of Lebanese pharmacy students found that self-reported stress and anxiety persisted at levels >30% one year after the transition to online learning. 18 …”
Section: Introductionmentioning
confidence: 99%